Fratture del femore prossimale - Capuano, N.; Carbone, F.; Del Buono, A. (Lo Scalpello - Journal, 2018)
PROXIMAL FRACURES OF THE FEMUR The goals of a tissue-preserving minimally invasive approach to the hip are to provide early short term recovery, achieve hip joint stability, minimise muscle strength loss from surgery, spare the peri-articular soft tissues, and allow for unrestricted motion in the long term. It is indicated in case of hip arthroplasty in patients with no pre-existing hardware, with a sufficient space between the acetabular rim and greater trochanter, and for the management of subcapital femoral fractures in older patients. Contraindications include protrusio acetabuli and joint stiffness. Starting from a lateral position, a 5–8 cm incision is made from the tip of the greater trochanter, followed by identification and transaction of the piriformis tendon. Anterior mobilization of the gluteus minimus follows, together with exposure and capsulotomy of the posterior superior of the capsule. We proceed then to prepare the acetabulum. After removal of the head and neck, we prepare the femoral canal. Complete muscle relaxion is helpful to proceed to satisfactory trial reduction. As regards postoperative management, patients may progress to motion and weight bearing without restriction. From April 2009 to December 2016, the first author (NC) operated on 820 patients for subcapital fractures of the femoral neck. Seven hundred (85%) patients could walk with full weight load within 24 hours from the operation, and climb stairs 24 hours later with low loss of blood, and fast recovery.